Carbon dioxide exchange of buds and developing shoots of boreal Norway spruce exposed to elevated or ambient CO2 concentration and temperature in whole-tree chambers - Hall, Marianne; Räntfors, Mats; Slaney, Michelle; Linder, Sune; Wallin, Göran (Tree Physiology, 2009)
Effects of ambient and elevated temperature and atmospheric carbon dioxide concentration ([CO 2 ]) on CO 2 assimilation rate and the structural and phenological development of shoots during their first growing season were studied in 45-year-old Norway spruce trees ( Picea abies (L.) Karst.) enclosed in whole-tree chambers. Continuous measurements of net assimilation rate (NAR) in individual buds and shoots were made from early bud development to late August in two consecutive years. The largest effect of elevated temperature ( T E ) was manifest early in the season as an earlier start and completion of shoot length development, and a 1–3-week earlier shift from negative to positive NAR compared with the ambient temperature ( T A ) treatments. The largest effect of elevated [CO 2 ] ( C E ) was found later in the season, with a 30% increase in maximum NAR compared with trees in the ambient [CO 2 ] treatments ( C A ), and shoots assimilating their own mass in terms of carbon earlier in the C E treatments than in the C A treatments. Once the net carbon assimilation compensation point (NACP) had been reached, T E had little or no effect on the development of NAR performance, whereas C E had little effect before the NACP. No interactive effects of T E and C E on NAR were found. We conclude that in a climate predicted for northern Sweden in 2100, current-year shoots of P. abies will assimilate their own mass in terms of carbon 20–30 days earlier compared with the current climate, and thereby significantly contribute to canopy assimilation during their first year.